the hardy boys mystery stories 58 the sting of the scorpion - Dixon, Franklin W.; Franklin W. Dixon (New York Grosset & Dunlap, 1979)
The Hardy Boys: The Sting of the Scorpion (#58) follows Frank and Joe Hardy as they investigate a terrorist gang sabotaging a new wild animal park and a dirigible company. After witnessing a dirigible explosion, the brothers, alongside friends like Chet Morton, uncover a conspiracy involving hidden enemies.
English